UTILIZATION OF DIGITAL PLATFORMS BY HALAL SMES: A QUALITATIVE ANALYSIS OF BUSINESS MANAGEMENT AND ITS IMPACT - Saifudin Saifudin; Andini Septi Liani; Siti Amalia Rahmawati; Isnadatul Fitria; M Anang Ma'ruf; Zidan Ataya Kausali; Haslenna Hamdan (IAIN Langsa, 2026)
This study explores the adoption and integration of digital platforms, such as e-commerce, social media, and financial technology, in MSME operations. It aims to identify managerial practices in the digital transformation process, examine MSME actors’ perceptions of the impact on business efficiency, market performance, and customer engagement, and determine the factors influencing digital platform effectiveness. Using a qualitative case study approach, the research focused on five MSMEs from various sectors, including culinary, retail, manufacturing, creative industries, and fashion. Data was collected through semi-structured interviews and analyzed with the N-Vivo 12 application. Findings indicate that digital platforms improve access to data from suppliers and customers, but challenges like delays and technical issues persist. The integration of digital systems with business partners offers significant benefits, although synchronization issues remain a barrier. Real-time data exchange enhances operational efficiency, yet technical challenges and varying technological skills among partners need attention. Information security, with encryption and two-factor authentication, is also a priority. The study suggests improvements in training and infrastructure to support MSMEs in adopting digital technologies, contributing to the understanding of digital platforms' impact on MSME growth and operations.